Association between early feeding of banana (Musa paradisiaca) and vomiting or abdominal distention in neonates - Hananto Wiryo; M Hakimi; A Samik Wahab; Pitono Soeparto (Paediatrica Indonesiana, 2004)
Objective To assess the relationship between banana given asearly solid food feeding and symptoms of intestinal obstruction (SIO)such as vomiting and abdominal distention among neonates.Methods A longitudinal cohort study was done in 1993 at a ruralcommunity of West Lombok District on Lombok Island, West NusaTenggara Province, Indonesia. There were 3420 neonates whowere followed up by interviewing their mothers until 28 days afterdelivery. The main outcome measure was the occurrence of SIO.Results Compared to infants who were not given solid food, therelative risk (RR) of SIO for infants given food other than bananaas early solid food feeding was 1.87 (95%CI 0.48;8.24), while forinfants given banana only as early solid food feeding, the RR was9.15 (95%CI 1.96;42.58). After the adjustments of birth weight, co-lostrum, and breast feeding, the odds ratio of SIO for infants givenbanana was 2.99 (95%CI 2.65;5.14).Conclusion Banana as early solid food for neonates feeding isan important risk factor for the occurrence of SIO